Modulating effects of plasma containing anti-malarial antibodies on in vitro anti-malarial drug susceptibility in Plasmodium falciparum - Monatrakul, Preeyaporn (BioMed Central, 2010)
BACKGROUND: The efficacy of anti-malarial drugs is determined by the level of parasite susceptibility, anti-malarial drug bioavailability and pharmacokinetics, and host factors including immunity. Host immunity improves the in vivo therapeutic efficacy of anti-malarial drugs, but the mechanism and magnitude of this effect has not been characterized. This study characterized the effects of 'immune' plasma to Plasmodium falciparumon the in vitro susceptibility of P. falciparum to anti-malarial drugs. METHODS: Titres of antibodies against blood stage antigens (mainly the ring-infected erythrocyte surface antigen [RESA]) were measured in plasma samples obtained from Thai patients with acute falciparum malaria. 'Immune' plasma was selected and its effects on in vitro parasite growth and multiplication of the Thai P. falciparum laboratory strain TM267 were assessed by light microscopy. The in vitro susceptibility to quinine and artesunate was then determined in the presence and absence of 'immune' plasma using the (3)H-hypoxanthine uptake inhibition method. Drug susceptibility was expressed as the concentrations causing 50% and 90% inhibition (IC(50 )and IC(90)), of (3)H-hypoxanthine uptake. RESULTS: Incubation with 'immune' plasma reduced parasite maturation and decreased parasite multiplication in a dose dependent manner. (3)H-hypoxanthine incorporation after incubation with 'immune' plasma was decreased significantly compared to controls (median [range]; 181.5 [0 to 3,269] cpm versus 1,222.5 [388 to 5,932] cpm) (p= 0.001). As a result 'immune' plasma reduced apparent susceptibility to quinine substantially; median (range) IC(50 )6.4 (0.5 to 23.8) ng/ml versus 221.5 (174.4 to 250.4) ng/ml (p = 0.02), and also had a borderline effect on artesunate susceptibility; IC(50 )0.2 (0.02 to 0.3) ng/ml versus 0.8 (0.2 to 2.3) ng/ml (p = 0.08). Effects were greatest at low concentrations, changing the shape of the concentration-effect relationship. IC(90 )values were not significantly affected; median (range) IC(90 )448.0 (65 to > 500) ng/ml versus 368.8 (261 to 501) ng/ml for quinine (p > 0.05) and 17.0 (0.1 to 29.5) ng/ml versus 7.6 (2.3 to 19.5) ng/ml for artesunate (p = 0.4). CONCLUSIONS: 'Immune' plasma containing anti-malarial antibodies inhibits parasite development and multiplication and increases apparent in vitro anti-malarial drug susceptibility of P. falciparum. The IC(90 )was much less affected than the IC(50 )measurement.